THE INFLUENCE OF PROFIT MANAGEMENT AND FINANCIAL PERFORMANCE ON COMPANY VALUE IN BUILDING MATERIALS CONSTRUCTION SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2018-2021 PERIOD - Muliani; Rico Nur Ilham; Chairil Akhyar; Siti Maimunah (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
This study examined the effect of earnings management, profitability, capital structure, and liquidity on the firm value in building materials construction sub-sector companies listed on the Indonesia Stock Exchange during 2018-2021. This study used secondary data in the form of financial statements of each company in the building materials construction sub-sector. The sample in this study consisted of 16 building materials construction sub-sector companies listed on the Indonesia Stock Exchange. The data analysis method used was multiple linear regression using Eviews 12. The results partially indicated showed that earnings management and liquidity had no significant effect on firm value, while profitability and capital structure had a positive and significant effect on firm value. Meanwhile, the simultaneous test results showed that earnings management, profitability, capital structure, and liquidity significantly affected firm value in building materials construction sub-sector companies listed on the Indonesia Stock Exchange from 2018 to 2021.